China's Regulatory State : A New Strategy for Globalization - Hsueh, Roselyn, 1977- (Book collections on Project MUSE., 2011)
In China's Regulatory State, Roselyn Hsueh demonstrates that China only appears to be a more liberal state; even as it introduces competition and devolves economic decisionmaking, the state has selectively imposed new regulations at the sectoral level, asserting and even tightening control over industry and market development, to achieve state goals. By investigating in depth how China implemented its economic policies between 1978 and 2010, Hsueh gives the most complete picture yet of China's regulatory state, particularly as it has shaped the telecommunications and textiles industries. Hsueh contends that a logic of strategic value explains how the state, with its different levels of authority and maze of bureaucracies, interacts with new economic stakeholders to enhance its control in certain economic sectors while relinquishing control in others. Sectoral characteristics determine policy specifics although the organization of institutions and boom-bust cycles influence how the state reformulates old rules and creates new ones to maximize benefits and minimize costs after an initial phase of liberalization. This pathbreaking analysis of state goals, government-business relations, and methods of governance across industries in China also considers Japan's, South Korea's, and Taiwan's manifestly different approaches to globalization.